Strength Training and the Young Athlete - Volk, E.
Some of the guidelines and recommendations to consider when training adolescent weight lifters: The young athlete should be mentally and emotionally mature. Be sure equipment is properly sized and modify the training according to the athlete's growth spurts. The first 6 to 12 weeks should consist of basic physical conditioning and learning techniques. Young athletes should not attempt weights that they cannot perform comfortably and with complete control. Training intensity and volume should be what the developing athlete's body can safely cope with. Emphasize correct technique and gradual progression. Stress to the young athlete that his or her success should be measured in technique perfection and general performance conditioning. Avoid sets consisting of high repetitions, especially with the Olympic lifts. Repetitions should only be performed with weights that allow the last rep to be rather easily executed. Never overtrain the young athlete to avoid overuse injuries and illness. Up to four workouts per week with one day of no lifting between workouts is recommended.